The "Exceptionalist Trap": Why the Future First Amendment Must Take Fundamental Human Rights into Account - Amy Kristin Sanders (Washington University Journal of Law & Policy, 2021)
Other countries do not have the same approach to freedom of expression as the United States. The American approach to freedom of expression wields influence around the world. Sanders argues the United States’ unwillingness to consider alternatives to the current categorical approach to free speech can no longer be justified. This Article explores the possibility of better aligning free expression jurisprudence in the United States with other liberal democracies. Sanders argues that alignment will result in the elevation of other human rights in the United States including privacy, dignity, and autonomy.
Keywords: First Amendment; free speech; freedom of expression; privacy; dignity; autonomy; human rights; United States